Penerapan Digital Marketing Dalam Mendukung Kegiatan Pemasaran Produk UMKM Masyarakat Bekare - Indriyani, Firly; Husna Ni'matul Ulya; Indah Trisna Nurhayati; Lidyyana Dwi Rahayu (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
Highly developed technology is utilized for various purposes, including by MSMEs. Some residents feel that technology has an impact on dependency, especially internet use. Utilization of the internet as a means of information technology to carry out business activities for MSMEs. The aim of this community service is to socialize the application of digital marketing to support product marketing for MSMEs in Bekare village, Bungkal subdistrict, Ponorogo district. The method used in this service uses the ABCD method, which provides digital marketing training assistance to MSMEs in Bekare Village. The results of implementing this activity are that mentoring has had a positive impact on the community and MSMEs in Bekare Village in the form of increasing sales, increasing brand awareness, strengthening skills, and improving product quality. In this training, the role of companions is very important in providing support, guidance and motivation for the Bekare Village community. With this community service, the people of Bekare Village can increase their knowledge about the use of social media as a means of introducing effective MSME products.